1986
DOI: 10.1095/biolreprod35.3.657
|View full text |Cite
|
Sign up to set email alerts
|

Magnum Morphogenesis during the Natural Development of the Quail Oviduct: Analysis of Egg White Proteins and Progesterone Receptor Concentration1

Abstract: The histological development of the quail oviduct and the changes in concentrations of progesterone receptor, ovalbumin, conalbumin, ovomucoid and ovoglycocomponents are analyzed during the period spanning 7-35 days of age. The initiation of luminal epithelial cell proliferation is the first event of magnum growth. The epithelial cells begin to evaginate into subepithelial stroma and form tubular glands. Meanwhile, luminal epithelium starts cellular pleomorphism through ciliogenesis. No egg white proteins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Tubular glands in immature quails were sparsely distributed, while glands in mature birds were compacted. Similar observations have been made in the oviductal regions of the immature and mature domestic fowl (Breen and De Bruyn, 1969;Palmiter and Wrenn, 1971), Japanese quail (Hoffer, 1971;Eroschenko, 1979;Pageaux et al, 1986;Berg et al, 2001), ostrich (Madekurozwa, 2002(Madekurozwa, , 2004 and rhea (Parizzi et al, 2008). A study by Yu and Marquardt (1973) has shown that the egg white protein ovalbumin is secreted by magnal tubular glands.…”
Section: Discussionsupporting
confidence: 71%
“…Tubular glands in immature quails were sparsely distributed, while glands in mature birds were compacted. Similar observations have been made in the oviductal regions of the immature and mature domestic fowl (Breen and De Bruyn, 1969;Palmiter and Wrenn, 1971), Japanese quail (Hoffer, 1971;Eroschenko, 1979;Pageaux et al, 1986;Berg et al, 2001), ostrich (Madekurozwa, 2002(Madekurozwa, , 2004 and rhea (Parizzi et al, 2008). A study by Yu and Marquardt (1973) has shown that the egg white protein ovalbumin is secreted by magnal tubular glands.…”
Section: Discussionsupporting
confidence: 71%
“…Epithelial-to-mesenchymal transition (EMT) endows cells with migratory and invasive properties, and plays an important role in developmental processes including tissue repair and differentiation [34]. Previously, Heryanto et al suggested that the tubular glands were generated by the invasion and cytodifferentiation of the mucosal epithelium and old glandular cells were replaced with newly derived GE during oviductal tissue remodeling [35], [36]. Our results suggest that up-regulation of cytokeratin is a defining factor for initiation of regeneration and plays a significant role in initial tissue remodeling of the reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol markedly stimulates this alkaline fraction and apparently shifts its optimal activity to a more neutral pH. In quails, natural or estrogen-induced development of the oviduct begins with the proliferation of the primitive luminal epithelium: epithelial cells evaginate into subepithelial stroma and form tubular glands (27,28). The identification of these changes requires further study.…”
Section: Discussionmentioning
confidence: 99%